1998
DOI: 10.1523/jneurosci.18-08-03098.1998
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mesocorticolimbic Neuronal Responses During Cocaine and Heroin Self-Administration in Freely Moving Rats

Abstract: To compare neuronal activity within the mesocorticolimbic circuit during the self-administration of cocaine and heroin, multiple-channel single-unit recordings of spike activity within the rat medial prefrontal cortex (mPFC) and nucleus accumbens (NAc) were obtained during the consecutive selfadministration of cocaine and heroin within the same session. The variety of neuronal responses observed before the lever press are termed anticipatory responses, and those observed after the lever press are called post-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
92
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(107 citation statements)
references
References 49 publications
14
92
0
1
Order By: Relevance
“…However, although BP 897 is more D 3 R-selective than most other available compounds, behavioral data must be interpreted with caution, since it exerts partial agonist activity and is endowed with a complex receptor-binding profile. Nevertheless, the present results are in keeping with studies indicating that different neurobiological mechanisms subserve the appetitive value of food and drugs of abuse, and that opiates and cocaine activate neuronal circuits that are in part different (Chang et al, 1998;Miyazaki et al, 1998;Carelli et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…However, although BP 897 is more D 3 R-selective than most other available compounds, behavioral data must be interpreted with caution, since it exerts partial agonist activity and is endowed with a complex receptor-binding profile. Nevertheless, the present results are in keeping with studies indicating that different neurobiological mechanisms subserve the appetitive value of food and drugs of abuse, and that opiates and cocaine activate neuronal circuits that are in part different (Chang et al, 1998;Miyazaki et al, 1998;Carelli et al, 2000).…”
Section: Discussionsupporting
confidence: 91%
“…Although one source of discrepancy between reports may be due, at least in part, to procedural differences (ie between-vs within-session extinction), these results might indicate that different neuronal circuits mediate a similar behavior driven by either drugs of abuse or natural reward. In fact, electrophysiological studies clearly indicated that cocaine, heroine, and food activated different neuronal populations in the NAcc (Chang et al, 1998;Miyazaki et al, 1998;Carelli et al, 2000). In contrast, rimonabant appears to reduce specifically the potentiation by quinelorane of the motivational strength of food pellets.…”
Section: Discussionmentioning
confidence: 99%
“…Although a growing body of evidence demonstrates some shared and some distinct molecular, cellular, and circuit mechanisms between psychostimulant and opiate action (Albertson et al, 2006;Badiani et al, 2011;Chang et al, 1998;Koo et al, 2012;Nestler, 2005), the contribution of D1-type vs D2-type NAc MSNs to morphine reward remains unknown.…”
Section: Introductionmentioning
confidence: 99%